Optimization of Parking Lot Stormwater Management: a Case Study - Sagit, Dilnaz (International Journal of Engineering and Management Sciences, 2025)
As urbanization accelerates, parking lots lead to stormwater runoff and localized flooding due to impervious layers and inefficient drainage. This case study evaluates stormwater management strategies across four parking lots in Debrecen, Hungary, to propose effective retrofitting solutions. The methodology combines visual site assessments with a comparative analysis of global best practices identified in the literature. Findings suggest integrating Green Infrastructure (GI) and Low Impact Development (LID) principles into parking lot design can enhance infiltration and significantly reduce surface runoff. Key recommendations include utilizing nearby vegetated depressions and replacing conventional concrete slabs with permeable surfaces. Beyond the flood avoidance, these strategies aim to reduce pressure on the local sewer system and minimize puddle formation.